Educational Technology-Based National Talent Management Model to Prepare the 2045 Golden Generation in Non-Formal Education - Somanedo, Ofri; Kurniawan, Didik; Chanifa, Arini Milla; Vitasari, Any Diana (Universitas Negeri Padang, 2025)
his study aims to analyze the role of national talent management in preparing Indonesia's golden generation 2045 in the non-formal education sector. The main focus of this research is how technology-based talent management, especially artificial intelligence (AI), can support the development of students' skills and potential. Using the Systematic Literature Review (SLR) approach, this study maps current trends and practices in talent management and identifies existing research gaps. Based on an analysis of 33 articles published between 2021 to 2025, the study found that the application of technologies such as Machine Learning (ML) and Deep Learning (DL) in e-recruitment and skills development has great potential to improve the efficiency and effectiveness of talent management. However, challenges related to cost, data privacy, and bias in algorithms remain major obstacles. Therefore, this study suggests that non-formal educational institutions continue to develop policies that focus on the integration of technology that is ethical, inclusive, and prioritizes data privacy, in order to support the achievement of the goals of Golden Indonesia 2045. Keywords: Talent Management, Non-Formal Education, Human Resource Development, Talent Development, Education Technology.